Binding of Hydrophobic Guests in a Coordination Cage Cavity is Driven by Liberation of "High‐Energy" Water. Issue 7 (30th November 2017) - Metherell, Alexander J.; Cullen, William; Williams, Nicholas H.; Ward, Michael D.
Abstract: Invited for the cover of this issue is the group of Michael D. Ward at the Universities of Warwick and Sheffield. The image depicts the 'hydrophobic effect' that is responsible for guest binding in the host cavity. Read the full text of the article at 10.1002/chem.201704163 . Abstract : " Using a combination of X‐ray crystallography and NMR studies, we have demonstrated the extensive host/guest properties of our cubic cage ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 1554 ff. (DOI:10.1002/chem.201704163 ).